Poem by Patricia Whiting, May, 1957 - Whiting, Patricia, 1940-2010:::Creator::::::::::::
Poem by Patricia Whiting titled, "He Who Stears the Nights Lantern." Two copies of the same poem are included, one of which has edits that were incorporated into the second copy.